Clinical Features of Aortitis with Gastrointestinal Involvement - Mansour Altuwaijri; Abdulmajeed Altoijry (Reviews in Cardiovascular Medicine, 2022)
Few vascultides have a predilection for the aorta. Among those are Takayasu arteritis, Behcet’s disease, giant cell arteritis, and infectious aortitis. Diagnosis of aortitis requires a high index of suspicion since clinical features are atypical and nonspecific. However, many patients present with gastrointestinal manifestations owing to mesenteric involvement, intestinal infarction, and hepatitis. The most common vascultides that involve the aorta are Takayasu arteritis, Behcet’s disease, giant cell arteritis, and infectious arteritis. Herewith, we review the literature on epidemiology, gastrointestinal manifestations, and management of each form of aortitis that affects the gastrointestinal tract.